Training and Mentoring on the Implementation of Structures Physical Exercise for People Aged 25-35 Years - Ningrum, Desy Tya Maya; Hafizah; Sundari, Sri; Mahyudi, Yafi Velyan; Azkiya, Aura Putri; Heryanto, Athira Shafa (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The productive age group of 25–35 years old faces the challenge of increasing sedentary behavior due to work demands, technology use, and limited time for physical activity. This condition has the potential to reduce physical fitness and increase the risk of non-communicable diseases. This community service activity aims to enhance the knowledge, skills, and awareness of the 25–35 age group in implementing Structured Physical Exercise in a planned, safe, and sustainable manner in their daily lives. The methods of implementation include training, mentoring, and evaluation. The training phase focused on providing material on the concept of structured physical activity, which includes frequency, intensity, time, and type of activity (FITT), as well as physical activity practices appropriate for young adults. The mentoring phase was carried out through direct guidance and monitoring of the implementation of structured physical activity in the daily routines of participants. Subsequently, the evaluation phase was conducted to assess changes in participants' level of understanding, participation, and consistency in performing physical activities. The results of the activity showed an increase in participants' knowledge and practice regarding the importance of structured physical activities consisting of upper body and lower body exercise programmes. In conclusion, this community service programme has successfully improved understanding and practice of structured physical exercise among the productive age group, and has laid a strong foundation for the implementation of more sustainable and systematic follow-up programmes.